2002
DOI: 10.1161/hq0402.105901
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Soluble Cellular Adhesion Molecules in Subjects With Low HDL-Cholesterol

Abstract: Abstract-The purpose of this study was to investigate whether the expression of cellular adhesion molecules (CAMs) is enhanced in individuals with low HDL cholesterol (HDL-C). Plasma levels of soluble vascular cell adhesion molecule-1 (sVCAM-1), intercellular adhesion molecule-1 (sICAM-1), and E-selectin (sE-selectin) were measured in subjects with low (below the 10th percentile for the Italian population), average, or high (above the 90th percentile) HDL-C. Average sICAM-1 and sE-selectin levels were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 56 publications
6
82
1
2
Order By: Relevance
“…Our results are consistent with other studies that have reported a negative correlation between the plasma concentration of HDLc and that of hsCRP in patients with low HDLc levels, but not in those with normal or elevated HDLc levels [23] [24].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with other studies that have reported a negative correlation between the plasma concentration of HDLc and that of hsCRP in patients with low HDLc levels, but not in those with normal or elevated HDLc levels [23] [24].…”
Section: Discussionsupporting
confidence: 93%
“…125 It was also found that the increase in HDL levels induced by treatment with fenofibrate was associated with a significant reduction in the plasma concentrations of sICAM-1 and sE-selectin. 125 It is unclear, however, whether the reduction in sICAM and sE-selectin was the consequence of the increase in HDL or a direct antiinflammatory effect of the fibrate on the artery wall.…”
Section: Clinical Implications Of Antioxidant/ Antiinflammatory Propementioning
confidence: 94%
“…In a study of subjects with a wide range of HDL cholesterol concentrations, it was found that the plasma levels of soluble ICAM-1 and soluble E-selectin (but not soluble VCAM-1) were significantly higher in subjects with low HDL levels compared with those with average or high HDL levels. 125 Furthermore, the concentration of HDL cholesterol correlated inversely with both soluble ICAM-1 (sICAM-1) and soluble E-selectin (sE-selectin) in the low-HDL subjects but not in those with normal or elevated HDL levels. 125 It was also found that the increase in HDL levels induced by treatment with fenofibrate was associated with a significant reduction in the plasma concentrations of sICAM-1 and sE-selectin.…”
Section: Clinical Implications Of Antioxidant/ Antiinflammatory Propementioning
confidence: 93%
“…125 Furthermore, the concentration of HDL cholesterol correlated inversely with both soluble ICAM-1 (sICAM-1) and soluble E-selectin (sE-selectin) in the low-HDL subjects but not in those with normal or elevated HDL levels. 125 It was also found that the increase in HDL levels induced by treatment with fenofibrate was associated with a significant reduction in the plasma concentrations of sICAM-1 and sE-selectin. 125 It is unclear, however, whether the reduction in sICAM and sE-selectin was the consequence of the increase in HDL or a direct antiinflammatory effect of the fibrate on the artery wall.…”
mentioning
confidence: 93%